It Flows from the Heart: Kiinoomaagewag nibi manidoog - Wall, Barbara Moktthewenkwe (Matrix, 2025)
Through a combination of reflective, creative, and academic writing in Anishinaabemowin and English, this research article explores Kiinoomaagewag nibi manidoog—Knowledge that originates with the water spirits—and the infinite, intimate relationship between water, Bodwewaadmii Anishinaabe women, the cosmos, and all of life. It explores Bodwewaadmii Anishinaabe women’s roles and responsibilities in the care taking of water, and the parallel responsibilities of the moon and water-related metaphysical beings. In addition, the concept of water and water spirits as relatives, teachers, and sustainers is discussed.